Recovery of water and reusable salt solution from reverse osmosis brine in textile industry: A case study - Recep Partal; Irfan Basturk; Selda Murat Hocaoglu; Ahmet Baban; Ecem Yilmaz (Water Resources and Industry, 2022)
Textile industry is one of the major water-consuming sectors; therefore, developing methods for reusing water is essential. Processes including reverse osmosis (RO) have gained momentum recently and been widely used. However, concentrated streams (brine) generated from RO must be managed properly. In this study, a pilot-scale brine treatment system containing ozone oxidation, nanofiltration (NF), RO and ion exchange (IEX) was developed and operated to recover a high quality process water and salt solution to be reused in dyeing processes. It was revealed that 77% of the water and 66% of the salt solution (as NaCl) can be recovered and brine discharge can be reduced. With full-scale operation for one year, it is possible to achieve cost-savings by 176,256 USD with 115,000 m3 reused water and by 37,000 USD with 680 tons of recovered NaCl. Recovery of brine makes it possible to achieve sustainable production and zero liquid discharge concepts.